2002
DOI: 10.1002/1522-2675(200208)85:8<2518::aid-hlca2518>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of an Enantiomerically Pure C2 Symmetric Ferrocenyl Carbene

Abstract: The straightforward, high-yield synthesis and X-ray structural analysis of the air-stable planar-chiral bis(ferrocenyl)carbene 1,3-bis-{(1R)-1-[(1R)-1-(trimethylsilyl)ferrocen-2-yl]ethyl}imidazol-2-ylidene (5) is reported. Compound 5 is obtained in four steps from the amine [(1R)-1-(dimethylamino)ethyl]ferrocene (1) upon diastereoselective silylation, methylation, nucleophilic substitution by imidazole, and deprotonation. The X-ray crystal structure of the free carbene shows the typical conformational features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 5 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that carbenes derived from benzimidazolium precursors exhibit the topology of an unsaturated N-heterocyclic carbene, but show spectroscopic and structural properties and the reactivity of carbenes with a saturated N-heterocyclic ring [3]. Previously, several examples of palladium(II) carbene complexes derived from benzimidazolium precursors with achiral [4] and chiral [5] alkyl groups or even the ferrocene moiety [6] adjacent to the nitrogen atoms have been reported. However, their potential application as phosphine free precatalysts remains relatively unexplored [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that carbenes derived from benzimidazolium precursors exhibit the topology of an unsaturated N-heterocyclic carbene, but show spectroscopic and structural properties and the reactivity of carbenes with a saturated N-heterocyclic ring [3]. Previously, several examples of palladium(II) carbene complexes derived from benzimidazolium precursors with achiral [4] and chiral [5] alkyl groups or even the ferrocene moiety [6] adjacent to the nitrogen atoms have been reported. However, their potential application as phosphine free precatalysts remains relatively unexplored [7].…”
Section: Introductionmentioning
confidence: 99%
“…This ferrocene imidazolium salt has been subsequently shown to act as an anion receptor [17,18]. Similarly, the general structure of the ferrocene substituted imidazolium salt has also been used to prepare chiral carbene ligands [19][20][21], Fig. 1(b) and (c).…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that nucleophilic substitutions on the α‐carbon atom in ferrocenyl compounds proceed with retention of the configuration of the stereogenic center 27. The analysis of the 1 H NMR spectra revealed that our diastereoisomer 12 [ δ =0.29 (TMS), 1.18 (CH 3 ), 2.36 (NMe 2 ), 3.34 (C α H), 4.12 ppm (Cp)] differs from compound ( R , S p )‐ 12 [ δ =0.26 (TMS), 1.22 (CH 3 ), 2.04 (NMe 2 ), 3.82 (C α H), 4.07 ppm (Cp)] reported in the literature 26b. Signs and values of the optical rotation match literature data (see the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 83%